2018
DOI: 10.3390/molecules23071812
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Postulated Cytotoxic Activity of Phenolic and Anthocyanin-Rich Fractions from Polana Raspberry (Rubus idaeus L.) Fruit and Juice—In Vitro Study

Abstract: In this study, the antioxidative and anti-inflammatory potential of crude extracts (CE), anthocyanin-rich fractions (ARF), and phenolic fractions (PF) from raspberry (R) and raspberry juice (J) were evaluated. The antioxidant properties were evaluated with three complementary assays: DPPH radical scavenging activity, chelating Fe(II) power, and ferric reducing power. The highest antioxidant activity was determined for the crude extract from raspberry pulp (RCE) in the case of all methods used. The anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…A number of Rubus species showed cytotoxic activity. For example, the fruits of Rubus chingii Hu showed cytotoxic activity against HepG2, Bel‐7402, A549 and MCF7 human cancer cell lines, while R. idaeus L. revealed higher cytotoxic activity towards the human leukaemia cell lines: J45 and HL60 . In the current study, R. takhtadjanii , like R. chingii, showed similar cytotoxic activity against HepG2 cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…A number of Rubus species showed cytotoxic activity. For example, the fruits of Rubus chingii Hu showed cytotoxic activity against HepG2, Bel‐7402, A549 and MCF7 human cancer cell lines, while R. idaeus L. revealed higher cytotoxic activity towards the human leukaemia cell lines: J45 and HL60 . In the current study, R. takhtadjanii , like R. chingii, showed similar cytotoxic activity against HepG2 cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, we selected red raspberry ( Rubus idaeus L.) as our experimental model plant because it is a species widely known for its edible fruits and as polyphenol rich and highly beneficial for human health [22,23]. Furthermore, they are most commonly known as food products and their extracts are also known as anti-inflammatory [24] and antimicrobial properties [25]. As mentioned above, numerous studies report increasing polyphenol content in various plants by light irradiation management.…”
Section: Introductionmentioning
confidence: 99%
“…In the gastric toxicity experiment, we showed that even by using a 100 times higher dose, ISP‐VT was less toxic than indomethacin. Data in the literature show that ISP‐VT natural analogue vanillic acid decreased levels of COX‐2 and inhibit activation of nuclear transcription factor‐κB (NF‐κB) (Kim et al, ; Rosa et al, ; Szymanowska, Baraniak, & Bogucka‐Kocka, ; Zduńska, Dana, Kolodziejczak, & Rotsztejn, ).…”
Section: Resultsmentioning
confidence: 99%